Effect of the restorative technique on load-bearing capacity, cusp deflection, and stress distribution of endodontically-treated premolars with MOD restoration - Daniel Maranha da Rocha; João Paulo Mendes Tribst; Pietro Ausiello; Amanda Maria de Oliveira Dal Piva; Milena Cerqueira da Rocha; Rebeca Di Nicoló; Alexandre Luiz Souto Borges (Restorative Dentistry & Endodontics, 2019)
ObjectivesTo evaluate the influence of the restorative technique on the mechanical response of endodontically-treated upper premolars with mesio-occluso-distal (MOD) cavity.Materials and MethodsForty-eight premolars received MOD preparation (4 groups, n = 12) with different restorative techniques: glass ionomer cement + composite resin (the GIC group), a metallic post + composite resin (the MP group), a fiberglass post + composite resin (the FGP group), or no endodontic treatment + restoration with composite resin (the CR group). Cusp strain and load-bearing capacity were evaluated. One-way analysis of variance and the Tukey test were used with α = 5%. Finite element analysis (FEA) was used to calculate displacement and tensile stress for the teeth and restorations.ResultsMP showed the highest cusp (p = 0.027) deflection (24.28 ± 5.09 µm/µm), followed by FGP (20.61 ± 5.05 µm/µm), CR (17.72 ± 6.32 µm/µm), and GIC (17.62 ± 7.00 µm/µm). For load-bearing, CR (38.89 ± 3.24 N) showed the highest, followed by GIC (37.51 ± 6.69 N), FGP (29.80 ± 10.03 N), and MP (18.41 ± 4.15 N) (p = 0.001) value. FEA showed similar behavior in the restorations in all groups, while MP showed the highest stress concentration in the tooth and post.ConclusionsThere is no mechanical advantage in using intraradicular posts for endodontically-treated premolars requiring MOD restoration. Filling the pulp chamber with GIC and restoring the tooth with only CR showed the most promising results for cusp deflection, failure load, and stress distribution.